Enhancement mechanisms of coal permeability under water saturated conditions using liquid nitrogen freeze thaw cycles - Xiaohan Qi; Yong Zhang; Shuangrong Hou; Tian Ning; Qiang Lv (Scientific Reports)
Abstract In order to investigate the effect of cyclic freeze-thaw of liquid nitrogen on the fracturing and permeability enhancement of water-rich coal seam, the conventional triaxial loading experiments and nuclear magnetic resonance (NMR) experiments after cyclic freeze-thaw of water-saturated coal samples were designed based on the HC-SPT-100 high-pressure triaxial experimental machine and nuclear magnetic resonance (NMR) analyzer with the raw coal from the coal mine in Wang zhuang as the experimental obje fissures ct to investigate the damage and seepage characteristics of the coal samples. Dried coal samples were used in the experiment for comparison purposes. The results showed that the peak stress of the coal samples showed a decreasing trend, the modulus of elasticity showed a decreasing trend, and the Poisson’s ratio showed an increasing trend with the increase of the number of liquid nitrogen cyclic freeze-thaw. The maximum elastic energy accumulated in the water-saturated coal samples was always lower than that in the dry coal samples during the loading process. The coal samples before and after liquid nitrogen freeze-thaw showed strain concentration phenomenon, and the stress concentration phenomenon of the coal samples was more obvious after water-saturated treatment. The effect of liquid nitrogen freeze-thaw on the fracturing and permeability of the water-saturated coal samples was more significant, and with the increase in the number of liquid nitrogen freeze-thaw cycles, the initial permeability of dry coal samples increases from 3.02 × 10− 3 µm2 to 6.06 × 10− 3 µm2while the initial permeability of saturated coal samples increases from 0.11 × 10− 3 µm2 to 6.93 × 10− 3 µm2. The experimental results can provide theoretical guidance for gas extraction in water-rich coal seam with more water.